KEANEKARAGAMAN DAN SEBARAN KUPU-KUPU (Lepidoptera: Rhacalopera) DI KAWASAN KAMPUS UNIVERSITAS SRIWIJAYA INDRALAYA SUMATERA SELATAN - Nirmila Sari, Syafrina Lamin, Doni Setiawan, (SEMIRATA 2015, 2015)
Research on diversity and distribution of butterflies, was held at the campus Indralaya Sriwijaya University of South Sumatera. The purpose of this study were to diversity and distribution of butterflies at the Sriwijaya University of Indralaya. The study used purposive and collection methods in November 2014-January 2015. Sampling sites were divided into five locations: Arboretum, Faculty of Science, Faculty of Law, Faculty of Agriculture and Tanjung Putus Swamp. The parameters used are the index of species diversity, dominance index and evenness index. The results showed that the diversity of butterflies in the region is classified as moderate. Overall found as many as 40 species of butterflies with a number of 609 individuals consisting of 5 the Papilionidae, Nymphalidae, Pieridae, Lycaenidae, and Hesperiidae. Regions Sriwijaya University has a diversity of butterflies that were moderate with criteria (H'1â‰¤H'â‰¤3), in each different habitat types, and not found butterfly species that dominate in every type of habitat in this Unsri region. Distribution of butterflies found in the campus area Unsri Indralaya categorized fairly evenly with a range of values from 0.58 to 0.68.Keywords: Butterfly, Diversity, Distribution , Sriwijaya University